Managing mass events and competitions with difficult-to-access locations using mobile electrocardiac monitoring. Issue 2 (September 2015) - Shih, Chun-Ming; Lin, Che-Wei; Clinciu, Daniel L.; Jian, Wen-Shan; Kuo, Terry B.J.; Nguyen, Phung Anh; Iqbal, Usman; Hsu, Chun-Kung; Owili, Patrick O.; Li, Yu-Chuan (Jack)
Abstract Objective Using mobile wireless technology to monitor ECG in participants of mass events and sports taking place in difficult-to-access location could both prevent and easier detect arrhythmias as well as provide real-time monitoring for any type of injury. We assessed the effectiveness of mobile wireless monitoring technology and IT in detecting possible emergencies during a skyscraper race. Methods We attached specially designed wireless surveillance biopatches on 120 individuals participating to monitor their continuous ECG and location during a skyscraper run-up race at Taipei 101 building, Taiwan. The outcomes of interest were detection of abnormal heartbeats and QRS waves indicative of possible cardiac problems and the exact location of participants during the occurrence of emergencies. Results The devices accurately sent over 50 warnings to our monitoring platform when both, danger limits were reached by competitors (<60 or >195 beats per minute) or competitors stopped moving, proving very effective in quickly detecting abnormities and alerting staff of possible emergencies at exact locations. Conclusion This efficient and inexpensive monitoring method can also prevent arrhythmias in unscreened competitors, the danger of collision among staff and competitors, and preserves oxygen by eliminating additional on-foot monitoring staff. Additionally, it could have multipurpose usage, especially during disasters and accidents occurring in difficult-to-access locations, in military exercises and personal monitoring.